Biology Of<i>Trypanosoma Cruzi</I> 2019
DOI: 10.5772/intechopen.86046
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Main Infective Stage ofT. cruziEnter and Avoid Degradation in Host Cells? A Description of the Pathways and Organelles Involved on These Processes

Abstract: Trypanosoma cruzi, the etiological agent of Chagas disease, is an intracellular parasite that targets specific proteins of the host cell resulting in the generation of a unique parasitophorous vacuole (PV). As an intracellular parasite, T. cruzi interacts with cells from the mammalian host. Here we review aspects related with the binding of the main infective developmental stage (trypomastigote) to the host cell and its recognition by surface-exposed ligands/receptors. This process involves numerous signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 107 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…The presence of T. lewisi polymorphism in the blood of rats in our study shows the establishment of an infective stage with the presence of both epimastigotes (development stage) and trypomastigotes (infectious stage; adult stage). This finding is interesting because epimastigotes are usually seen in the midgut of invertebrate vectors such as flies [ 19 ] and rarely in maintenance hosts [ 20 ]. It may be possible that stages of T. lewisi development occur in both maintenance host and invertebrate vectors compared to its closest relatives, such as Trypanosoma cruzi [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of T. lewisi polymorphism in the blood of rats in our study shows the establishment of an infective stage with the presence of both epimastigotes (development stage) and trypomastigotes (infectious stage; adult stage). This finding is interesting because epimastigotes are usually seen in the midgut of invertebrate vectors such as flies [ 19 ] and rarely in maintenance hosts [ 20 ]. It may be possible that stages of T. lewisi development occur in both maintenance host and invertebrate vectors compared to its closest relatives, such as Trypanosoma cruzi [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…(17,18) Activation of signaling pathways during the initial parasite-host cell interface stage promotes T. cruzi entry by cytoskeleton-dependent or -independent processes. (5) FAK, which is involved in cytoskeleton regulation, (19) is activated during T. cruzi cardiomyocyte invasion. (7) In the present study, we identified HSPG as protagonists in triggering the FAK signaling pathway during T. cruzi cell entry.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Different T. cruzi invasion mechanisms involving IP3-kinase activation, lysosome recruitment (including oligopeptidase B and cruzipain-mediated), sphingomyelinase-mediated membrane repair and autophagic pathways, as well as host cell cytoskeleton mechanisms, have been described. (5) Many cellular signaling pathways have been reported as driving parasite entrance, including protein kinase activation. (5) The activation of focal adhesion kinase (FAK), a non-receptor tyrosine kinase, may be subverted by diverse intracellular pathogens, (6) including T. cruzi.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Thus, the trypomastigotes invade all nucleated cells by an endocytic process mediated by multiple ligand/receptor and signaling systems. 4 Intracellularly, trypomastigotes escape from the parasitophorous vacuole, and convert to amastigote forms that are the multiplicative stage found in vertebrate hosts. After several binary division cycles, amastigotes differentiate back into trypomastigotes, which are the main forms released after the rupture of infected host cells.…”
mentioning
confidence: 99%